Localized radiotherapy of solid tumors using radiopharmaceutical loaded implantable system: insights from a mathematical model - Piranfar, Anahita; Souri, Mohammad; Rahmim, Arman; Soltani, Madjid (Frontiers in Oncology, 2024)
Computational models provide valuable insights into biological interactions that may not be fully understood through experimental approaches. Here we investigate an innovative 3-dimensional spatiotemporal model designed for simulating the controlled release and dispersion of radiopharmaceutical therapy (RPT) using prostate-specific membrane antigen (PSMA) targeted radiopharmaceutical, 177 Lu-PSMA, within solid tumors through a dual-release implantable delivery system. The primary objective is to examine the spatial and temporal distribution of radiopharmaceuticals within the tumor and its host tissue, along with the evaluation of the impact of various parameters, including hypoxia region extension, binding affinity, and initial drug amount, on the concentration of radiopharmaceutical agents within the tumor microenvironment. Because of device position at center of the tumor, the analysis demonstrates that the tumor region exhibits a significantly higher area undercurve of total concentration compared to the surrounding normal tissue. Furthermore, low density of microvascular in extended hypoxia regions result in increased drug availability owing to reduction in drug elimination by microvascular, promoting enhanced binding to PSMA receptors and improved therapeutic effectiveness. The reduction of the dissociation constant (KD) leads to heightened binding affinity, increasing bound and internalized drug concentration.In regard with the effect of initial radioactivities (7.1×10 7 , 7.1×10 8 , and 7.1×10 9 [Bq]), the activity 7.1×10 8[Bq] emerges as the most promising choice, as it demonstrates a favorable balance between potent tumor cell elimination and minimized impact on normal tissues. These findings emphasize the potential of this local radiopharmaceutical delivery strategy, and highlight the important role of released drugs in relation to the radiation source (implant) for effective treatment of tumors. The findings of this study can serve as a valuable reference for future and experimental investigations, aiming to minimize the necessity for in vivo testing and guide the design of optimal medication protocols in clinical trials.